Aldehyde Dehydrogenase 6 Family Member A1 Facilitates Ti Implant Osseointegration in Hyperlipidemia. - Wang, Ya‐nan; Yu, Lu; Liu, Yingxue; Xu, Xin; Zhang, Dongjiao; Liu, Shiyue; Ge, Shaohua (Oral Diseases, 2025)
Objective: Hyperlipidemia seriously impairs titanium (Ti) implant osseointegration, and endogenous therapeutic targets remain elusive. Aldehyde dehydrogenase 6 family member A1 (ALDH6A1) plays an important role in redox regulation and lipid metabolism. However, its role in osseointegration under hyperlipidemia conditions has not been thoroughly investigated. This study aimed to elucidate the potential role of ALDH6A1 in implant osseointegration in hyperlipidemia mice. Materials and Methods: ALDH6A1 expression levels were detected in peri‐implant tissue and in primary osteoblasts by qRT‐PCR and western blot. The role of ALDH6A1 in reducing oxidative damage and improving osseointegration on Ti implant surface was evaluated by locally overexpressing ALDH6A1 with a lentiviral vector in peri‐implant tissue in hyperlipidemia mice. Results: ALDH6A1 expression significantly decreased in hyperlipidemia mice, compared with normal mice (p < 0.05). ALDH6A1 was downregulated in a high‐fat environment, and silencing ALDH6A1 led to osteogenic dysfunction in osteoblasts. ALDH6A1 overexpression maintained redox homeostasis and osteogenic activity of primary osteoblasts and facilitated osseointegration in hyperlipidemia mice by reducing oxidative damage in peri‐implant tissue. Conclusion: ALDH6A1 is a key protein for facilitating osseointegration by alleviating reactive oxygen species levels in hyperlipidemia, and developing specific ALDH6A1 agonists would be a promising strategy for ameliorating osseointegration in hyperlipidemia patients.